A Digital Platform Car Wash Business - Ndlovu, Cebo (University of the Witwatersrand, Johannesburg, 2023)
The Car Wash Digital Platform (App) is a new business venture that addresses the problem of customers needing a convenient car wash service. This study was aimed at evaluating the viability of this new business venture. A customer discovery was conducted using an online survey to test if potential customers would be interested in such a service. The customer discovery was only made on the end user customer who would request the car wash service. The customer discovery for the service providers was not completed due to time limitations. This project's competitive advantages include the convenience it will provide to its clients in addition to fuel and mileage saved by not having to drive to a particular car wash facility. The time saved from driving to and from the car wash service provider is another competitive advantage of this business venture. The New Business Venture adopted the Lean Business Canvas as its business strategy model. The data from the online survey contributed to mapping the Lean Business Canvas. The marketing strategy was developed by using the marketing mix of customer segmentation, the 4 Ps of marketing, and Porter’s five forces model. The financial analyses indicated that the new business venture could break even in its first year of operation and generate an estimated Net Profit Margin of 40% by the fourth year
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Digital platform; Car wash; Business; SDG-9: Industry, innovation and infrastructure